The Effect of Adherence to Mediterranean Diet on Disease Activity in Patients with Inflammatory Bowel Disease - Çelik, Kevser; Güveli, Hakan; Erzin, Yusuf; Kenger, Emre Batuhan; Özlü, Tuğçe (Turkish Journal of Gastroenterology, 2023)
Background: Mediterranean diet, owing to its infla mmati on-mo dulat ory effects, is considered a beneficial dietary regimen for patients with inflammatory bowel disease. Despite promising results in the literature, studies on this subject are still limited. Therefore, the aim of this study was to evaluate adherence to the Mediterranean diet in patients with inflammatory bowel disease and examine its impact on disease activity and quality of life. Methods: A total of 83 patients were included in the study. Mediterranean Diet Adherence Scale was used to evaluate adherence to the Mediterranean diet. Crohn’s Disease Activity Index was used to evaluate disease activity in Crohn’s disease. Disease activity was determined by using the Mayo Clinic score for ulcerative colitis. Quality of Life Scale Short Form-36 was used to evaluate the quality of life of patients. Results: When the median Mediterranean Diet Adherence Scale score was 7 (1-12), only 18 patients (21.7%) showed strong adherence to the Mediterranean diet. Disease activity scores of patients with ulcerative colitis having low adherence to the Mediterranean diet were found to be higher (P < .05). In addition, some quality of life parameters were relatively higher in patients with ulcerative colitis who showed strong adherence to the Mediterranean diet (P < .05). For Crohn’s disease, no significant difference was found in disease activity and quality of life with respect to adherence to the Mediterranean diet (P > .05). Conclusions: Stronger adherence to the Mediterranean diet in patients with ulcerative colitis can help improve quality of life and modulate disease activity. However, further prospective studies are needed to investigate the potential use of the Mediterranean diet in inflammatory bowel disease management.